The three‐pillar matrix of patient blood management. (April 2015) - Isbister, J. P.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="quotation" id="voxs12135-blkfxd-0001" position="anchor" orientation="portrait"> 'Muse before you Transfuse' </boxed-text> For the majority of patients undergoing uncomplicated elective surgery, and in most cases of cancer chemotherapy, it should be possible to minimize or avoid blood transfusion by a standard of care that focuses on the management of a patient's own blood by optimizing and preserving haematopoietic reserves and tolerating deficiencies in reserves. Patient blood management is not an intervention or an alternative to allogeneic blood transfusion; it is sound evidence‐based clinical practice. Patient blood management improves clinical outcomes and as a corollary minimizes or avoids unnecessary allogeneic blood transfusions, reduces risks and helps contain health costs. The use of some autologous transfusion techniques, erythropoiesis‐stimulating agents and antifibrinolytic agents may be regarded as transfusion alternatives, but also bring with them potential hazards and costs that need balancing in the same manner as the decision to transfuse. Managing the triad of haematological risk factors for surgical patients, that is anaemia, haemorrhage and transfusion, is addressed by focusing on the three pillars of patient blood management. Maximizing total red cell mass, minimizing blood loss and tolerating of anaemia are of the essence. Most of the core principles of patient blood management come from a sound understanding of physiological and pathophysiological knowledge of haemopoiesis, haemostasis and oxygen transport and the causative mechanisms of the well‐understood hazards of blood transfusion. The concept of personalized medicine is best epitomized by Sir William Osler in his aphorism: 'It is much more important to know what sort of a patient has a disease than what sort of a disease a patient has'.